Salivary Microflora and Its Diagnostic Importance - Dina Rahmi Solihad Nasution; Zulham Yamamoto (Buletin Farmatera, 2022)
Saliva as a source of DNA has several advantages over blood. These advantages include easier sample collection, the sampling process can be carried out independently by participants, and stability. The study of the normal microflora of human saliva is increasingly in demand because it is related to the oral health status of each individual. Several studies explain microflora associated with diabetes, cancer, rheumatic heart disease, and others. Other things that affect the composition of the microflora of each individual include living habits, hygiene, age, and smoking. The microflora in saliva are protozoa, bacteria, yeast, and viruses. In healthy people, the characteristics of normal oral microflora found are dominant Gram-positive cocci and rods such as Actinomycetes spp and Streptococcus spp. Protozoa commonly found in saliva are Entamoeba gingivalis and Trichomonas tenax, while from the yeast Candida albicans group, the viruses most commonly found in saliva are herpes and retrovirus. Identification of normal salivary microflora can be done through microbiological and biomolecular approaches. Identification of microflora using a biomolecular approach, currently the most commonly used markers are 16S rRNA (bacteria) and ITS rDNA (fungi).